The Effect of Guided Imagery on Insomnia in the Elderly in the Jara Mara Pati Technical Implementation Unit (UPT) Kab. Buleleng - Aprilyawan, Grenda; Wibowo, Tri Suryo (Journal Of Nursing Practice, 2021)
Background: The aging process is a natural process faced by humans where there is a decrease or change in physical, emotional, psychosocial conditions which will certainly affect their productivity. This situation tends to have the potential to cause health problems, one of which is insomnia. There are some serious effects on sleep disorders such as excessive daytime sleepiness, impaired attention and memory, mood, depression, and decreased quality of life.Purpose: This study aimed to determine the effect of giving guided imagery to insomnia in the elderly at the Technical Implementation Unit (UPT) Jara Mara Pati Kab. Buleleng.Methods: The research design used was pre-experimental with a one-group pre-test post-test design. The population in this study were all elderly people who experienced insomnia in the Technical Implementation Unit (UPT) of Jara Mara Pati Kab. Buleleng with a sample size of 36 respondents, by using a simple random sampling technique. Data collection using a checklist sheet. The data obtained were then coded, scored, tabulated, and analyzed with the Wilcoxon test with a significant value of 0.05.Results: The results of this study show the results of value < which means that there is an influence of guided imagery on insomnia in the elderly.Conclusion: Seeing the results of this study can be used as non-pharmacological therapy by the elderly in (UPT) Jara Mara Pati Kab. Buleleng to improve sleep quality which is done once a month on a scheduled basis